(untitled) (Scientific journal of the Fergana State University, 2023)
With the financial support of the Ferghana City, in 2022, excavations were carried out on the arch of the ancient settlement of Kuva. The excavations were carried out in order to determine the internal and external structure of the pre-Mongolian and post-Mongolian acropolis. The excavations were carried out to obtain new historical and cultural data.